Revision of the Liriomyza blechi species group (Diptera: Agromyzidae) - Lonsdale, Owen (Zootaxa, 2026)
The Liriomyza blechi group is redefined and revised. Twenty-seven species are recognized, 16 of which are described here as new: L. biloba Lonsdale & Eiseman, L. borboros Lonsdale, L. furvunca Lonsdale, L. halomma Lonsdale, L. hyalina Lonsdale, L. orta Lonsdale, L. paspali Lonsdale & Eiseman, L. platypeos Lonsdale, L. pons Lonsdale, L. quadraticaia Lonsdale, L. samara Lonsdale, L. sphaericaia Lonsdale, L. strigiformis Lonsdale, L. telistyla Lonsdale, L. trispicula Lonsdale and L. zophodes Lonsdale. Most species occur in the Neotropics, with a minority extending into, or restricted to the temperate regions of North and South America. All species are (re)described, and a key, illustrations and photographs are provided. Host usage is still largely unknown, with rearing records available for a minority of species. Liriomyza avicenniae is strictly monophagous, known from a single host species (Avicennia germinans (L.) L.). Aside from L. philadelphivora on Philadelphus species (Hydrangeaceae), those taxa for which data are available occur on the dicot Order Lamiales and/or the subfamily Panicoideae (Poaceae). Rearing data are relatively abundant for several species that feed on both of these distant lineages of monocots and dicots in a form of disjunctive oligophagy, indicating a novel pattern of agromyzid host usage that might be more widespread within the group. The Japanese L. philadelphi Sasakawa is discussed.